The Severity of Menstrual Dysfunction as a Predictor of Insulin Resistance in PCOS - Brower, Meredith; Brennan, Kathleen; Pall, Marita; Azziz, Ricardo (The journal of clinical endocrinology and metabolism, 2013)
Objective:The objective of the study was to evaluate the relationship between the severity of menstrual disturbances and the degree of insulin resistance in women with polycystic ovary syndrome (PCOS).Design:This was a cross-sectional study.Setting:The study was conducted at a tertiary care academic medical center.Patients:Four hundred ninety-four women diagnosed with PCOS by the Rotterdam criteria and 138 eumenorrheic, nonhirsute, control women participated in the study.Interventions:Interventions in the study included history and physical examination and blood sampling.Main Outcome Measure(s):Physical assessment and total and free T, dehydroepiandrosterone sulfate, fasting glucose, and insulin levels and calculated homeostatic model assessment values for insulin resistance (HOMA-IR) were measured.Results:Overall, 80% of PCOS subjects included had clinically evident oligomenorrhea. The remainder demonstrated vaginal bleeding intervals of fewer than 35 days (ie, with either polymenorrhea or clinically apparent eumenorrhea). Only 10% of PCOS subjects studied were ovulatory. After adjusting for body mass index, age, and race, all PCOS subjects with menstrual cycles longer than 35 days had significantly higher mean HOMA-IR levels than controls, and those with cycles longer than 3 months had the highest HOMA-IR levels. There was no difference in mean HOMA-IR levels between PCOS with regular vaginal bleeding (apparent eumenorrhea), regardless of whether they were anovulatory or not, or those with cycles fewer than 26 days, when compared with controls.Conclusions:Women with PCOS and overt oligomenorrhea comprise the vast majority of PCOS subjects seen clinically and have significantly more insulin resistance than controls. About 20% of PCOS women seen reported vaginal bleeding intervals of fewer than 35 days in length and did not generally have overt insulin resistance, regardless of whether they were ovulatory or not. Overall, the presence of clinically evident menstrual dysfunction can be used to predict the presence and possibly the degree of insulin resistance in women with PCOS.